Święto „Tygodnia Dziecka” jako jedna z form działalności Polskiego Komitetu Opieki nad Dzieckiem w II Rzeczypospolitej - Wróblewska, Urszula; Gołko, Joanna (Biuletyn Historii Wychowania, 2018)
The aim of this article is to discuss “the Children’s Week” event organised from 1926 by the Polish Childcare Committee, which was the prototype of today’s Children’s Day and Mother’s Day. This issue has not been the subject of scientific analysis. The aim, meaning and course of “the Children’s Week” in the Second Republic of Poland were analysed based on the interwar sources’ materials. This holiday was one of the social events organised by the Polish Childcare Committee, which, as a body of the Ministry of Labour and Social Care, was responsible for improving health and social conditions of children and teenagers. Therefore, it organised care units for mothers and children, published scientific papers, propagated tasks related to the care of children and teenagers, and organised and conducted exemplary care institutions. “The Children’s Week” was a social event, which aim was to make Poles more interested in the situation of children and teenagers. For seven days the importance of proper care of the youngest children in a rebuilding country was emphasised. Every day was devoted to education or upbringing issues as well as the functioning of schools and social centres. The Children’s Day was on the first day of the event, and the Mother’s Day on the last. “The Children’s Week” in the Second Republic of Poland proceeded in accordance with the programme prepared by the Polish Childcare Committee. Each Voivodeship office tailored the programme to their capabilities and regional conditions. Despite the criticism it attracted, “the Children’s Week” was an extremely important social event, which was supported by pedagogical authorities, among others, Janusz Korczak. Annually, the public attention was focused on childcarerelated issues for seven days. This event was in line with the European trends at that time, in which children’s rights and freedoms were gaining more and more supporters.